The essence of domestic violence: Introductory issues - Bereznowska-Bulas, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article addresses the essence of domestic violence. A detailed analysis of the issue of domestic violence undoubtedly first requires an understanding of the mechanism of violence itself, in the common understanding of this phenomenon, and an indication of its types, because all domestic violence is a type of violence, but not all violence can be classified as domestic violence. The article includes, in particular, the definitions of domestic violence used by the authors of various legal publications, from the perspective of criminology, as well as those used by the legislator. The author also presents issues related to types of violence and characteristics of perpetrators of domestic violence, concluding with current statistics on the topic.
Keywords: domestic violence; types of violence; characteristics of perpetrators of domestic violence; mechanism of violence